Employee retention and talent management at a sugar mill in South Africa - Pierre Joubert (Problems and Perspectives in Management, 2017)
Talent shortage due to failure by organizations to retain staff with the necessary expertise is becoming a reality and it is important that this challenge is addressed expeditiously. This article focuses on the relationship between employee retention and talent management at a sugar mill with a view to ascertaining whether or not the organization is possibly the reason for employees to leave. The study involved investigating and highlighting the need and importance of talent management, including the attraction and retention of staff with necessary skills. The study touched on the importance of competitive incentives and rewards in the attraction and retention of employees. A survey was conducted among 137 employees. Data were analyzed by means of descriptive and inferential (correlations and regressions) statistics. The interpreted results indicated that staff satisfaction leads to high productivity and plays a significant role in the retention of staff. The results further indicated that management strategies are not being used to the extent that they should be in the retention of talent, whilst most respondents felt that fringe benefits that used to be offered by the organization had a positive influence on staff satisfaction and on the retention of talented employees. The study revealed a commonly held perception by the non-designated group that people from designated groups use the provisions of the Employment Equity Act to find better opportunities with other organizations.